2013
DOI: 10.1063/1.4826095
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Ultrafast vibrational dynamics of hydrogen bond network terminated at the air/water interface: A two-dimensional heterodyne-detected vibrational sum frequency generation study

Abstract: Ultrafast vibrational dynamics of hydrogen bond network at the air/water interface is revealed by two-dimensional heterodyne-detected vibrational sum frequency generation (2D HD-VSFG) spectroscopy. Three diagonal peaks are clearly observed in the 2D HD-VSFG spectrum, which correspond to the negative and positive hydrogen-bonded OH stretch bands and the positive “free” OH stretch band in the steady-state HD-VSFG spectrum. A diagonally elongated bleaching lobe of the hydrogen-bonded OH at 0 ps indicates that it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 26 publications
3
60
0
4
Order By: Relevance
“…Given that no ion pairing occurs for the studied salts 35,36 , that the volume taken by a bare Na þ ion is B6/B11 times smaller than that of a bare Cl À /I À ion (ionic radius of sodium: 1.02 Å), and that the sodium ions are hardly present in the probed surface layer 11,15,16,24 , we neglect the effect of the cation in calculating interfacial concentrations. We derive an effective interfacial concentration of chloride of (2.0/1.81) 3 Our findings are of fundamental importance for processes in atmospheric chemistry. Specifically, it has recently been shown that significant levels of atmospheric iodine originate from the interfacial chemistry at the oceans interfaces, and is associated with ozone reduction 5 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Given that no ion pairing occurs for the studied salts 35,36 , that the volume taken by a bare Na þ ion is B6/B11 times smaller than that of a bare Cl À /I À ion (ionic radius of sodium: 1.02 Å), and that the sodium ions are hardly present in the probed surface layer 11,15,16,24 , we neglect the effect of the cation in calculating interfacial concentrations. We derive an effective interfacial concentration of chloride of (2.0/1.81) 3 Our findings are of fundamental importance for processes in atmospheric chemistry. Specifically, it has recently been shown that significant levels of atmospheric iodine originate from the interfacial chemistry at the oceans interfaces, and is associated with ozone reduction 5 .…”
Section: Discussionmentioning
confidence: 95%
“…We measure the vibrational energy relaxation dynamics of the OD groups at the surface of salt solutions using time-resolved IR-pump/SFG-probe spectroscopy 3,[21][22][23] . In this technique, an IR excitation (pump) pulse excites OD groups at a specific vibrational frequency, and the effect of that excitation is followed in time with the SFG probe pair (for details see Methods).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[40][41][42][43][58][59][60][61] Therefore, the orientation analysis presented here can be directly applied to these spectral regimes. In addition, since only the diagonal cuts of HD 2D VSFG are analyzed to obtain the orientation heterogeneity, in principle, the same method can be applied to IR pump-SFG probe experiments 38 when there is no coupling between vibrational modes.…”
Section: Resultsmentioning
confidence: 99%
“…This new advancement solves the long-standing "magic angle" challenge in 1D VSFG spectroscopy. With the growing popularity of HD 2D VSFG spectroscopy in the surface science community, [39][40][41][42][43][44]47,49,[58][59][60][61][62][63] this new method will contribute significantly in determining the molecular conformations at interfaces.…”
Section: Resultsmentioning
confidence: 99%